Unfortunately, the browser used by Answers.com for posting questions is incapable of accepting mathematical symbols. This means that we cannot see the mathematically critical parts of the question. We are, therefore unable to determine what exactly the question is about and so cannot give a proper answer to your question.
-8x+7 = -7x-2 -8x = -7x-2-7 -8x=-7x-9 -8x+7x=-9 -1x=-9 x=-9/-1 x=9
If you mean: 7x = 49 then the value of x is 7
3x = 7 - 4x 3x + 4x = 7 - 4x + 4x 7x = 7 7x/7 = 7/7 x = 1
7x+3=10 7x=7 {subtract 3 from each side} x=1 {divide each side by 7}
13 - 3X = 4X + 1add 3X to each side13 - 3X + 3X = 4X + 3X + 113 = 7X + 1subtract 1 from each side13 - 1 = 7X + 1 - 112 = 7Xdivide both sides integers by 712/7 = (7/7)X12/7 = X=========check in original equation13 - 3(12/7) = 4(12/7) + 113 - 36/7 = 48/7 + 113 and 1 need to be converted to fractions ( 13 * 7 = 91, so/ 91/7 = 13 ; 1 = 7/7 )91/7 - 36/7 = 48/7 + 7/755/7 = 55/7==============checks
If you mean: 7x+91 then it can be factored to 7(x+13)
7x - 5 = -13 + 56Perform the indicated addition on the right side of the equation:7x - 5 = 43Add 5 to each side:7x = 48Divide each side by 7 :x = 48/7 = 6 6/7
Solving ln(7x) = ln(13) for x is really easy.First, exponentiate both sides of the equation with the mathematical constant, e (2.71828):eln(7x) = eln(13), which reduces to 7x = 13.Now, divide both sides of the equation by 7:(7/7)x = 13/7.This gives us the answer x = 13/7, or 1.857.You may have noticed that the exponentiating step was just a formality as the terms inside of the ln brackets had to be equal, so we could have simply started at 7x = 13.
6x2 + 7x = 56x2 + 7x - 5 = 0x =[ -7 ± √[72 - 4(6)(-5)] ]/2(6)x = [-7 ± √(49 + 120)]/12x = (-7 ± √ 169)/12x = (-7 ± 13)/12x = (-7 + 13)/12 or x = (-7 - 13)/12x = 6/12 = 1/2 orx = -20/12 = - 5/3
7x-4y= 13 3x-y= 7 we have two equations we need to find the y, because it is by him self. and now for finding the y we transpose -y eqaul to 7 -3x then subt to equation 1 7x-4(7-3x)= 13 7x -28 + 12x= 13 combine like terme 7x +12x -28 =13 19x -28 = 13 +28 +28 19x= 41 19x/19 = 41/19 x= 2.15 now find the y 7(2.15) - 4y= 13 15.0.5 -4y = 13 -15.05 -15.05 -4y=-2.05 -4y /-4 y=-0.5125 the solution is ( 2.15, 0.5125)
6
7x + 29 = 36 7x + 29 - 29 = 36 - 29 7x = 7 7x/7 = 7/7 x = 1
x=-7/13
None. 7x - 1 is not equal to 7x - 7.
7x + 7 = 7(x + 1)
4x - 13 = 22 - 3x add 3x to both sides 7x - 13 = 22 add 13 to both sides 7x = 35 divide both sides by 7 x = 5
7x+7=28x 28x-7x=7 21x=7 x=3